Investigation of Genetic Mutations in High-risk and Low-risk Basal Cell Carcinoma in a Non-Caucasian Population by Whole Exome Sequencing - Hyun Jee Kim; Minho Lee; Young Bok Lee; Dong Soo Yu (Medical Journals Sweden, 2021)
This study analysed genomic mutations in basal cell carcinoma using whole exome sequencing of DNA specimens obtained from 20 Korean patients. Histological evaluation determined that 15 (75%) were low-risk basal cell carcinomas, and 5 (25%) were high-risk basal cell carcinomas. Seventy-five percent of the basal cell carcinomas harboured somatic mutations in hedgehog pathway genes (PTCH1, 40% and SMO, 50%) and 45% harboured mutations in TP53. LRP1B was the most frequently mutated gene in high-risk basal cell carcinomas, SMO was the most frequently mutated gene in low-risk basal cell carcinomas. Specifically, LRP1B, ROS1, PTCH1, KMT2C, NSD1 and ARID1A mutations were more frequent in high-risk basal cell carcinomas than in low-risk basal cell carcinomas. However, copy number gains of the ROS1 gene were observed only in low-risk basal cell carcinomas. Other basal cell carcinoma related genes found in this study include: KDR, KMT2D, FAT1, FAT4, GRIN2A, ERBB4, NOTCH2, PDE4DIP, TET1, ZFHX3 and PREX2. These results provide insight into basal cell carcinoma in non-Caucasians.